(untitled) (Journal of Education and Development, 2019)
Higher education has faced many challenges since its meager inception. However, higher education today faces its greatest combinations of challenges: economic uncertainty, accountability, globalization and emerging technologies that are daunting to learn and intimidating to implement. VUCA accurately describes this complex, evolving and dynamic environment confronted by global higher education. Therefore, global higher education institutions are attempting to develop the capacity to adapt and modify the new models of knowledge, information and change. In the Industrial Era, work got done in silos with adherence to process and the cult of efficiency. However, this type of working will no longer suffice in an era characterized by flux and change–the VUCA world.